Electromagnetic performance analysis of flux-switching permanent magnet tubular machine with hybrid cores - Shaopeng Wang; Chengcheng Liu; Youhua Wang; Gang Lei; Youguang Guo; Jianguo Zhu (CES Transactions on Electrical Machines and Systems, 2020)
The performance of traditional flux switching permanent magnet tubular machine (FSPMTM) are improved by using new material and structure in this paper. The existing silicon steel sheet making for all mover cores or part of stator cores are replaced by soft magnetic composite (SMC) cores, and the lamination direction of the silicon steel sheet in stator cores have be changed. The eddy current loss of the machine with hybrid cores will be reduced greatly as the magnetic flux will not pass through the silicon steel sheet vertically. In order to reduce the influence of end effect, the unequal stator width design method is proposed. With the new design, the symmetry of the permanent magnet flux linkage has been improved greatly and the cogging force caused by the end effect has been reduced. Both 2-D and 3-D finite element methods (FEM) are applied for the quantitative analysis.